1986
DOI: 10.1038/jcbfm.1986.121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of γ-Hydroxybutyrate on the Reactivity of Pial Arteries before and after Ischemia

Abstract: Summary: The effect of "{-hydroxybutyrate (GHB) on the reactivity of pial arteries to local metabolic factors was tested in chloralose-anesthetized cats before or after a pe riod of transient ischemia induced by air embolism. The vascular reactions were determined during the perivas cular microapplication of artificial CSFs with in creasing concentrations of adenosine (10-11_ 10-3 M), H + (pH 5.1-7. 6), or K + (0-JO mM). During nonischemic conditions the pial arterial reactivity to adenosine and H+, but not to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
2
5
1
Order By: Relevance
“…In the present study, no increase in cerebral metabo lism was found. In conjunction with our previous findings of an increased cerebrovascular reactivity under experimental conditions identical with those of the present study (Haller et al, 1986), our data do not support the concept of a direct relationship be tween cerebral metabolism and cerebrovascular re activity.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In the present study, no increase in cerebral metabo lism was found. In conjunction with our previous findings of an increased cerebrovascular reactivity under experimental conditions identical with those of the present study (Haller et al, 1986), our data do not support the concept of a direct relationship be tween cerebral metabolism and cerebrovascular re activity.…”
Section: Discussioncontrasting
confidence: 57%
“…For the comparison of the global measurements during the control phase and after GHB, multivariate analysis of variance (MANOV A) with mixed effects was employed as previously described (Haller et al, 1986). The Statis tical Package for the Social Sciences (SPSSX) (Nie et al, 1983) was used for the computations.…”
Section: Statisticsmentioning
confidence: 99%
“…The concentration-response curves and the changes in vascular diameter between the two experimental phases (control/after air embolism) were analyzed as previously described [10], using multi variate analysis o f variance (MANOVA) with mixed effects. For the computation the program MANOVA o f the SPSS' package was used [11], A level o f p < 0.05 was accepted as significant in all statistical tests.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial blood pressure was continuously recorded from a catheter in a femoral artery, and the acid-base status was checked at regular intervals; the adjacent vein was cannulated for the continuous infu sion o f Tyrode's solution. A catheter was advanced into the innom inate artery via the right axillary artery to induce arterial cerebral air embolism as previously described [10]. After the animals had been put into a stereotaxic frame, a right temporoparietal craniotomy was performed, and the cortical surface was visualized under a thick layer of warmed paraffin oil.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation